Optimization of power flow in a local electrical network using phase shift transformers - yousef, batoul (Latakia University Journal -Engineering Sciences Series, 2025)
The use of phase shift transformer to control the active power flow in three-phase power transmission network is an alternative to new investment in high-cost overhead lines. The control of the active power flow is achieved by adjusting the phase angle of the voltage at the transformer terminals, In this research, we chose a local network within the coastal area of ​​230 Kv to control the flow of actual power after the Zeizoun station went out of service, as this led to an increase in the load of the Baniyas-Jableh line from 78% to 96% of its nominal load limit, using a phase shift transformer to ensure the operation of the electric power transmission lines within the permissible load limits and to ensure the continuity of the electric supply in a reliable manner. The case of installing a phase shift transformer on the Baniyas-Lattakia line was studied, after the Zizoun station was taken out of service. It was found that by controlling the transmission voltage angle, optimum power flow was achieved, represented by loading all electrical power transmission lines within their nominal load limits. where the actual power percentage transmitted through the Baniyas-Jableh line was reduced from 96% to 91% at the expense of increasing the load of the Baniyas-Lattakia line from 80% to 91% of its nominal load value, by adjusting the phase angle between the input and output voltages of the transformer at a value of 2.3°, The network operation simulation with and without phase shift transformer is performed using Power World Simulator software, according to the simulation results, the busbar voltages and angles, active power flow values ​​in the lines and total losses are calculated.